Livelihood security through integrated farming systems: A novel approach for farmers under Haroti region - Tetarwa, J P; Yadav, Rakesh Kumar; Ram, Baldev; Singh, Mahendra; Dhaka, B L; Singh, Pratap (Indian Farming, 2023)
Ghanshyam Yadav a conventional farmer having 3.25 ha of land was practicing an aged-old traditional crop-based farming, viz. cereals, oilseeds and pulses for the livelihood of his family. Through on-farm trainings and demonstration of IFS model, he adopted Integrated Farming System approach in his own field. Gradually, he has shifted from conventional crop-based farming to IFS with the components, viz. high value field crops (soybean, wheat, potato), two-tier horticulture system (guava + papaya + vegetables) and livestock (buffalo, cow) and other complementary/ supplementary enterprises (vermicomposting, diversified green fodder) under the close supervision of multi-disciplined scientists of Agriculture University, Kota. By adopting IFS model, he earns manyfold income instead of traditional farming. He is generating more employment and regular income as compared to conventional practices on the same piece of land. Moreover, in future, he is expecting more returns through this approach and inspiring other rural youth and farmers of his own and nearby villages in the Haroti region of Rajasthan.